The Analysis of Service Performance of Indonesia Syariah Bank (BSI) Customer Service To Its Customer’s Satisfaction - HM. Anwar (LPMP Imperium, 2021)
Customer service is the face of a bank. So that the quality of service provided affects the perception of bank customers. Bank Syariah Indonesia (BSI) customer service is different from conventional bank customer service. Conventional bank customer service usually looks according to company rules, while customer service at Islamic banks must prioritize Islamic appearance rather than attractiveness. Based on the foregoing, the authors are interested in conducting research on the satisfaction of BSI customers who look Islamic but can provide optimal satisfaction to their customers. This study uses statistical tests such as classical assumptions, hypotheses, correlations and regression with a sample of 100 respondents. The result of this research is that the service performance of BSI's customer service in Ciputat branch has no significant effect on customer satisfaction.